Relationship between motivational factors and employees’ performance for primary school teachers / Shahira Farina Jaafar - Jaafar, Shahira Farina (Faculty of Business and Management, 2017)
Majority of organizations are competing to survive in this volatile and fierce market environment. Motivational factors are considered as a force that drives the employees toward attaining specific goals and objectives of the organization. Nowadays, it is one of the sizzling issues in organizations since every organizations wants to make best use of their financial and human resources. This paper aims to analyze the most dominant motivational factor in enhancing employee performance. Data is collected from 127 employees by using self-administered questionnaire. Regression analysis is applied to find the most dominant factors on employee’s performance involving three variables self-efficacy, intrinsic motivation, and work relations. On the other hand, there is a relationship between motivational factor and employees’ performance, reflected in numerous studies. The literature shows that factors such as self-efficacy, intrinsic motivation, and work relations enhance employee performance. If the motivational factor is increased, their performance to work will also improve, as well as their accomplishments and the organizational performance. Nevertheless, employee that lack of motivation caused by either internal or external factor might weaken the employee performance. Therefore, not all individuals are the same, so each one should be motivated using different strategies. For example, one employee may be motivated by intrinsic motivation, while another might be motivated by work relations.